Nematofauna of red piranha pygocentrus nattereri (Kner, 1958) (characiformes: Serrasalmidae) from Amazonia, Brazil - Morais, Aprigio Mota; Cárdenas, Melissa Querido; Malta, José C.O. (Revista Brasileira de Parasitologia Veterinaria, 2019)
Between March and October 2008, 355 specimens of Pygocentrus nattereri were collected from the lowland lakes of Central Amazonia, Brazil, to study their nematode fauna. A total of 1.116 specimens of Nematoda were collected, belonging to six species. Procamallanus (Spirocamallanus) inopinatus was the species with the highest parasite indices. Larvae of Anisakis sp. have zoonotic potential and were found parasitizing the intestine and liver of Pygocentrus nattereri. Some of these nematode species were new records for the host P. nattereri. The diversity of nematodes that use P. nattereri as a host indicates the important role of this fish species in the maintenance of these six nematode species in the lowland lakes of Central Amazonia. © 2019, Brazilain Coll Veterinary Parasitology. All rights reserved.
Nematofauna de piranha-vermelha Pygocentrus nattereri (Kner, 1958) (Characiformes: Serrasalmidae) da Amazonia, Brasil
Keywords: Amazona; Anisakis; Biodiversity; Fauna; Helminth; Human Tissue; Intestines; Lake; Larva; Liver; Nonhuman; Serrasalmidae; Animals; Biodiversity; Characiformes; Classification; Female; Isolation And Purification; Male; Nematode; Parasitology; Animal; Biodiversity; Characiformes; Female; Male; Nematoda